1998
DOI: 10.1136/ip.4.3.203
|View full text |Cite
|
Sign up to set email alerts
|

Are life vests worn? A multiregional observational study of personal flotation device use in small boats: Table 1

Abstract: Objective-Although life vest use is thought to prevent drowning, their use by boaters has not been described. This study sought to determine the use of personal flotation devices (PFDs) in small boats. Methods-Boaters were observed between April and June 1995 in Washington andOregon and classified by their age, gender, PFD use, and boat type. Results-Among 4181 boaters, 25% wore a PFD. Use was highest in <5 year olds (91%) and lowest in those over 14 years (13%). Those in kayaks were most likely (78%) and thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
4

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 6 publications
2
21
0
4
Order By: Relevance
“…Observed life jacket use was low (30.7%) and relatively unchanged compared with state observations from 2000 (29%) and 1995 (24%) 11. This lack of progress is consistent with USCG observations of life jacket use across the US.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Observed life jacket use was low (30.7%) and relatively unchanged compared with state observations from 2000 (29%) and 1995 (24%) 11. This lack of progress is consistent with USCG observations of life jacket use across the US.…”
Section: Discussionsupporting
confidence: 72%
“…Prior observations in Washington State mirror these national trends. In 2000 an estimated 29% of Washington State boaters wore a life jacket,10 a slight increase from 25% in 1995 11…”
Section: Introductionmentioning
confidence: 99%
“…One observational study revealed that 90% of children younger than 5 years wore life jackets, but only 13% of those 14 years or older used a life jacket. 52 Reasons commonly cited for not wearing a life jacket include beliefs that there is a low risk of drowning, that life jackets restrict movement, that life jackets are uncomfortable, that life jackets are unattractive, and that wearing a life jacket is a sign of fear. 53 Parents of children who do not always wear life jackets report reasons including (1) the parent is in close proximity to the child, (2) a PFD for the child is on board in case of emergency, and/or (3) the child has good swimming skills.…”
Section: Boatingmentioning
confidence: 99%
“…Recreational boaters form a substantial proportion of drowning deaths in Australia,1 the USA,2 Canada3 and European countries 4. Personal flotation devices (PFDs), commonly called life jackets or life vests, are designed to prevent drowning by keeping the wearer afloat thereby increasing the likelihood of survival and rescue.…”
Section: Introductionmentioning
confidence: 99%